MECHANISMS OF SOCIAL MEDIA INFLUENCE ON ADDICTIVE BEHAVIOR OF YOUTH - Bogićević, Dragana; Popović-Ćitić, Branislava (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2025)
Social media have a major influence on the daily lives of individuals, which is reflected above all in the shaping of social attitudes, the acceptance of behavioral norms and the construction of one’s own identity. Children and youth are the most susceptible to this influence. Social media has not only brought numerous benefits, but also numerous risks for the mental health and behavior of young people. Indeed, social media has become a convenient place for marketing and sharing information about the use of psychoactive substances and gambling. The aim of this article is to point out the importance of social media as a factor that can influence the manifestation of addictive behaviors in youth. A systematic review of the literature found that social media influence the manifestation of addictive behavior in youth by presenting content, changing norms and attitudes, and providing opportunities for easier participation in risky activities. Frist, when young people are exposed to content related to drugs and gambling, they are more likely to engage in such behaviors. Second, content that promotes risky behavior, especially when such behavior is deemed acceptable by the (online) peer group, has the effect of changing individuals’ norms and attitudes towards normalizing the manifestation of such behavior. Finally, social media provides easier access to psychoactive substances and gambling in various ways, which contributes to young people becoming more involved in problematic behavior. The above-mentioned knowledge about the mechanisms of influence of social media can be used as an important resource in the prevention of various types of addictive behavior among youth.